The reliability of DIVA test based on M2e peptide exceed those based on HA2 or NS1 peptides - Tarigan, Simson; Sumarningsih, . .; Ignjatovic, J. (Indonesian Animal Sciences Society, 2015)
One of the most important disadvantage of vaccination against avian influenza is that it cannot protect vaccinated birds against infection. When vaccinated poultry are heavily exposed to the virus, prolonged, unrecognised, subclinical infection may persist on the farm. The condition can only be serologically monitored by a DIVA (differentiation of infected from vaccinated animals) test, whereas conventional diagnostic tests cannot be used. The DIVA tests based on an antibody response following virus replication is the most appropriate approach. For H5N1 influenza such antibodies includes those to the M2e and NS1 proteins and an epitope on the HA2 subunit (HA_488-516). The purpose of this study was to compare the magnitude of the antibodyÂ response in chickens vaccinated and infected with an H5N1 virus strain. For that purpose, sera collected from naÃ¯ve, vaccinated and infectedÂ birds, at 1, 2-3, â¥4 weeks post challenge were used. Antibodies were measured by ELISA using biotinylated synthetic peptides as coating antigens. The peptides used include four NS1 peptides corresponding to different regions of the NS1 protein and HA_488-516and M2e peptides. Peptides were coated onto microtitre plates either directly or via a streptavidin bridge. The results showed that vaccination did not cause antibody conversion to any of the peptides, where as challenged birds developed a high antibody response to M2e but, low response to the NS1 and HA2 peptides. Antibodies to the later peptides were detected only by the streptavidin-peptide ELISA. The ELISA based on NS1 or HA_488-516 peptides, therefore, are not reliable for use as DIVA test in H5N1 avian influenza virus infection. Key Words: M2e, NS1 Protein, HA2 Peptide, DIVA Test, H5N1